2009
DOI: 10.1099/vir.0.010660-0
|View full text |Cite
|
Sign up to set email alerts
|

Location of antigenic sites recognized by monoclonal antibodies in the influenza A virus nucleoprotein molecule

Abstract: The locations of amino acid positions relevant to antigenic variation in the nucleoprotein (NP) of influenza virus are not conclusively known. We analysed the antigenic structure of influenza A virus NP by introducing site-specific mutations at amino acid positions presumed to be relevant for the differentiation of strain differences by anti-NP monoclonal antibodies. Mutant proteins were expressed in a prokaryotic system and analysed by performing ELISA with monoclonal antibodies. Four amino acid residues were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For this reason, CTL specific to NP of PR8 virus is also able to kill H9N2 viral infected cells and mediate cross-protection. Since less is known about the B cell epitope on NP and its conservative property [43], the role of NP-specific antibodies (IgG and sIgA) in cross-protection is not clear yet. The more broad-spectrum cross-protection induced by DNA prime-intranasal protein boost strategy based on NP, such as cross-protection against highly pathogenic avian influenza H5N1 virus and pandemic H1N1 2009 influenza A virus, will be further evaluated in our future study.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, CTL specific to NP of PR8 virus is also able to kill H9N2 viral infected cells and mediate cross-protection. Since less is known about the B cell epitope on NP and its conservative property [43], the role of NP-specific antibodies (IgG and sIgA) in cross-protection is not clear yet. The more broad-spectrum cross-protection induced by DNA prime-intranasal protein boost strategy based on NP, such as cross-protection against highly pathogenic avian influenza H5N1 virus and pandemic H1N1 2009 influenza A virus, will be further evaluated in our future study.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular extracts were prepared, quantified for protein concentrations, and subjected to sodium dodecyl sulfate - polyacrylamide gel electrophoresis and subsequent Western blotting as described previously ( Li, 2009 ). For immunodetection, we used the following monoclonal (mAb) and polyclonal (pAb) antibodies: mouse anti-IAV NP mAb 5/1 ( Varich et al, 2009 ); Rabbit anti-TRIM21 mAb (Cell Signaling Technology); rabbit anti-IFIT1/ISG56 pAb ( Wang et al, 2009 ); rabbit anti-IFIH1/MDA5 pAb (Proteintech); rabbit anti-DDX58/RIG-I pAb (Enzo Life Sciences); mouse anti-Vinculin mAb (Proteintech); and appropriate IRDye® secondary antibodies - goat anti-mouse IgG IRDye® 680RD or goat anti-rabbit IgG IRDye® 800CW (both from LI-COR Biosciences). Protein bands were visualized with an Odyssey infrared imaging system (LI-COR Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…XunGui et al reported a B-cell epitope 243-251 AA of the H1N1 influenza A virus strain A/California/04/2009 (CA/04), which was highly conserved [24]. Natalia L. et al reported that the NP monoclonal antibody recognized four amino acid residues located at 236, 305, 372 and 470, and that the AAs at 305, 372 and 470 were highly conserved [25]. Gui-Rong B et al established a sensitive assay using an anti-NP antibody and recognized epitopes 59-130 AA in the NP protein [26].…”
mentioning
confidence: 99%